2016
DOI: 10.5897/jphe2015.0777
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Schistosoma and other parasites among female residents of some communities in Oyo State, Nigeria

Abstract: Prevalence of Schistosoma and other parasitic infections in 507 females (5-78 years) was determined in a cross-sectional study undertaken in seven communities of Oyo State, Nigeria. Urine and stool samples were examined, and 25.2% overall parasite prevalence was recorded. Schistosoma haematobium and Schistosoma mansoni prevalence was 5.5 and 0.3% respectively. Ascaris lumbricoides (11.4%), Hookworm (9.3%), Strongyloides stercoralis (0.6%), Trichuris trichiura (0.3%), Taenia saginata (1.2%) and Entamoeba histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Realizing that availability of such information is crucial in identifying and implementing effective control measures to prevent infection [33][34][35], this study intends to identify feasible strategies that will protect residents in the study area from infections from Bulinus and Lymnaea snails. However, studies have shown that the complex schistosome life cycle and the intricate interactions that are encountered with the host immune system make it difficult for neither drugs nor vaccines to adequately control schistosomiasis [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Realizing that availability of such information is crucial in identifying and implementing effective control measures to prevent infection [33][34][35], this study intends to identify feasible strategies that will protect residents in the study area from infections from Bulinus and Lymnaea snails. However, studies have shown that the complex schistosome life cycle and the intricate interactions that are encountered with the host immune system make it difficult for neither drugs nor vaccines to adequately control schistosomiasis [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Transmission of schistosomiasis depends on the extent and duration human-water contact (Ofulla et al, 2013). The women working frequently in water and domestic chores are at greater risk (Awobode et al, 2016). Morbidity and mortality are mostly associated with teenagers, young adults, women and infections in schoolage children (Rollinson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms developed by the disease included fever, headache, abdominal pain, malaise, urticarial and diarrhea (Awobode et al, 2016). Transmission of schistosomiasis depends on the extent and duration human-water contact (Ofulla et al, 2013).…”
Section: Introductionmentioning
confidence: 99%